Blood, Monstrosity and Violent Imagery: Grand-Guignol, the French Theatre of Horror as a Form of Violent Entertainment - Tanja Jurković ([sic])
During the sixty-year period of its existence, Grand-Guignol, the French theatre of horror, gained a status of a legendary theatre which dealt with horrors and terrors of human mind, successfully connecting faits divers (common, everyday facts) with the erotic and titillating scenes of violence on stage. The performance style, the writing, the special effects, and the directorship over the course of years, made this theatre a legendary place where blood flowed in streams and people fainted during performances, in this way making its indelible mark in horror genre today. In this paper, the author is trying to focus the attention on the theatre of Grand-Guignol as a form of violent entertainment and the way the representations of violence and horror enacted on its stage affected the audience, through Goldstein’s theory of the importance of visual imagery in different media today. Furthermore, through comparison of violent acts presented on the stage of the Grand-Guignol and the atmosphere they create in the viewer’s mind with some of the aspects of Artaud’s vision of his theatre of cruelty, the author attempts to show how this form of violent entertainment in the theatrical media influences the vision of that same violence within the audience, with the sense of security as the main idea in which the viewers feel safe to enjoy, envision and in a way become the participants in the performances enacted on the small stage of the Grand-Guignol.